Correlation of Clinical, Radiological and Endoscopic Grading of Adenoid Hypertrophy in Paediatric Population: A Cross-sectional Study - Ishi Jain; Pushkar Khare (International Journal of Anatomy Radiology and Surgery)
Introduction: Adenoid hypertrophy is one of the most common conditions encountered by Ear, Nose and Throat (ENT) surgeons in the paediatric age group. Clinical assessment of adenoid hypertrophy is the first step, but to confirm the degree of adenoid hypertrophy, both X-ray soft-tissue neck and endoscopy are needed. Aim: To correlate the clinical grading of adenoid hypertrophy with endoscopic and radiological findings. Materials and Methods: This was a hospital-based cross-sectional analytical study conducted at Chhatrapati Shivaji Subharti Hospital Meerut, Uttar Pradesh, India from August 2023 to January 2024. A total of 50 children aged between 4 and 15 years, who presented to the outpatient department of ENT with signs and symptoms of adenoid hypertrophy, were evaluated. These children underwent clinical evaluation, followed by endoscopy and X-ray lateral view of the soft-tissue neck. Adenoid hypertrophy was graded clinically, endoscopically and radiologically. Statistical analysis was performed using Kendall’s tau correlation analysis. Results: In the study population, the majority of children 17 (34%) were between the ages of 7 and 9 years, with a male predominance of 32 (64%). Grade-3 adenoid hypertrophy was the most common finding, observed in 21 (42%) based on clinical grading, 26 (52%) on endoscopy, and 19 (38%) on X-ray lateral view of the soft-tissue neck. There was a strong correlation between endoscopic and clinical grading (p-value=0.001), and the correlation between radiological and endoscopic grading was highly significant (p-value=0.001). Clinical grading and radiological findings also showed a significant correlation (p-value=0.002). Conclusion: All three modalities of adenoid grading are correlated and reliable. They can be used in different combinations for grading adenoid hypertrophy and determining the management plan.